2020
DOI: 10.1038/s41593-020-0627-5
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic regulation of Z-DNA in the mouse prefrontal cortex by the RNA-editing enzyme Adar1 is required for fear extinction

Abstract: DNA forms conformational states beyond the right-handed double-helix; however, the functional relevance of these non-canonical structures in the brain remains unknown. We show that, in the prefrontal cortex of mice, the formation of one such structure, Z-DNA, is involved in the regulation of extinction memory. Z-DNA is formed during fear learning, and reduced during extinction learning, which is mediated, in part, by a direct interaction between Z-DNA and the RNA editing enzyme Adar1. Adar1 binds to Z-DNA duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Potential Z-DNA regions change conformation from B to Z in response to a signal, and then must change it back to B-form. Dynamic formation of Z-DNA in response to fear was observed, and Z-DNA serves as a fast regulator of gene expression levels 53 . Moreover this process is reversible in a short period of time, and level of Z-DNA in the locus of interest was reduced after fear extinction training.…”
Section: Discussionmentioning
confidence: 99%
“…Potential Z-DNA regions change conformation from B to Z in response to a signal, and then must change it back to B-form. Dynamic formation of Z-DNA in response to fear was observed, and Z-DNA serves as a fast regulator of gene expression levels 53 . Moreover this process is reversible in a short period of time, and level of Z-DNA in the locus of interest was reduced after fear extinction training.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of p150 in both the cytosol and the nucleus is consistent with the nucleocytoplasmic shuttling of p150 [ 67 69 ]. Recent surveys of normal tissues show that p150 is mostly nuclear in murine thymus, spleen and prefrontal cortex [ 70 72 ]. Conversely, the cytoplasmic localization during stress of ADAR p110 isoform that lacks the Z-DNA binding domain, is not often referenced [ 73 ].…”
Section: Why Is the Science Of Non-b-dna Structures Difficult?mentioning
confidence: 99%
“…A recent study of the ADAR Zα regulation of fear extinction in mice found that 80% (97/122) of RNA editing sites overlap with Adar1 DNA binding, with an overrepresentation of SINE/LINE elements nearby. Both DNA binding and RNA editing were absent when a loss-of-function Zα (N175A/Y179A) mutant was tested in the in vivo assay [ 70 ]. This response also depends upon prion formation by the cytoplasmic polyadenylation element binding protein CPEB3 [ 103 ].…”
Section: Z-fliponsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, since experimental data supporting that retroelements are direct targets of the Zα domain are lacking in these studies, other possibilities should remain valid. In fact, another recent study showed that in the mouse prefrontal cortex, the Zα domain of ADAR1 recognizes Z-DNA in host genomes to control gene expression during fear learning ( 52 ).…”
Section: Future Perspectivesmentioning
confidence: 99%